DIRECTIONS OF MINIMIZATION OF FINANCIAL SCAMS IN THE FIELD OF PUBLIC PROCUREMENT - KYRYLENKO, Olga; RUSIN, Victor (Scientific journal «World of Finance», 2020)
Introduction. Ukraine is undergoing an extremely important and complex process of forming a modern and effective public procurement system aimed at creating a competitive environment and further developing fair competition in public procurement, as well as ensuring compliance with international obligations by consistently adapting Ukrainian legislation to EU standards. The task of public procurement reform is to significantly reduce financial fraud in this area and achieve savings in public funds.The purpose of the article is to analyze the process of reforming the public procurement in Ukraine, focusing on the latest changes, substantiation of proposals for ways to minimize financial fraud in the field of public procurement.Results. The main milestones of formation and improvement of the public procurement system in Ukraine are considered. Emphasis is placed on the features of the current stage, which are to create better conditions for bidders and prevent financial fraud in public procurement, expanding the list of violations and strengthening penalties. Data on the most common types of violations among procurement customers are given.Conclusions. The existing risks of unfair competition in procurement are indicated and the ways of minimizing financial fraud in this area are substantiated. Emphasis is placed on the importance of preventive measures that can be used to detect violations before the conclusion of the contract. In the context of strengthening the effectiveness of control measures, it is proposed to introduce a direct rule of criminal liability for violations in the field of public procurement. The implementation of the proposed measures will help increase the effectiveness of public policy in the field of public procurement, which will ultimately allow for more economical and efficient use of public funds.